A study on common problems in high rise residential building (PPR flat house) / Nurul Nabila Azhar - Azhar, Nurul Nabila (2021)
This research study is to show the common problems that occur in high rise building especially for PPR flat residential house in PPR Flat Taman Manggis, Georgetown, Pulau Pinang. The common problems that arise around in this residential building has been there for a long time and most often problems that arise in that building. Beside, from the common problems that has been identify, a few causes that lead to the common has been listed and also the solutions of the common problems. For this study, the method to obtain data from the public community is through online questionnaire form and also interview but using social media platform such as ‘Whatapps’ due to the sudden outbreak of Pandemic COVID-19 in Malaysia. The data obtain from the research study stated that most common problems that occur in case study is Malfunction Elevator. Furthermore, the occupants in that building knows the common problems that has been happening in their building but not all of them know about the causes of the common problems. It can be concluded that regular inspection on that building by the responsible parties can take care of the existing common problems and prevent new problems that may arise in that building.